Epidemiology of Kaposi's sarcoma. - Beral, V (1991)
The AIDS epidemic drew attention to KS, a previously rare and little studied condition. The epidemiological evidence summarized here strongly suggests that the disease is caused by a transmissible agent, in addition to HIV. Sexual contact is the most important mode of transmission of the agent, although transmission by blood and perinatally may also occur (Beral et al, 1990).